Human‐geographic effects on variations in the population genetics of Sinotaia quadrata (Gastropoda: Viviparidae) that historically migrated from continental East Asia to Japan. Issue 15 (15th July 2020) - Ye, Bin; Saito, Takumi; Hirano, Takahiro; Dong, Zhengzhong; Do, Van Tu; Chiba, Satoshi
Abstract: Background: Anthropogenic factors potentially affect observed biogeographical patterns in population genetics, but the effects of ancient human activities on the original patterns created by natural processes are unknown. Sinotaia quadrata, a widely distributed freshwater snail species in East Asia, was used to investigate this issue. It is unclear whether S. quadrata in Japan was introduced from China and how different human uses and varying geographic patterns affect the contemporary population genetics between the two regions. Thus, we investigated the demography of S. quadrata and detected its genetic structure in Japan and continental East Asia. Results: Sinotaia quadrata populations first naturally migrated from continental East Asia to Japan, which is associated with the ancient period in Japanese geohistory (about 70, 000 years ago). They were then artificially introduced in association with agriculture expansion by human movements in two recent periods (about 8, 000 and 1, 200 years ago). Populations in different parts of Japan have their own sources. Natural migration in the ancient period and artificial introduction in the recent period suggest that the population distribution is affected by both the geohistory of East Asia and the history of human expansion. In the background of the historical migration and introduction, contemporary populations in the two regions show different genetic patterns. Population divergence levels were significantly correlated with geographical patterns in Japan and significantly correlated with human interventions variables in continental East Asia, suggesting that long‐term geographical isolation is likely the major factor that shaped the contemporary population genetics in Japan, while modern human uses are likely the major factor in continental East Asia. Conclusions: Our preliminary results show a complex demography and unusual genetic patterns in the contemporary populations for a common freshwater snail and are of significance to determine the historical formation and contemporary patterns of biogeography in Japan and continental East Asia. Abstract : We document the population history and genetic history of the common freshwater snail Sinotaia quadrata in Japan and continental East Asia. Natural migration in the ancient period and artificial introduction in the recent period suggest that the population distribution is affected by both the geohistory of East Asia and the history of human expansion. Long‐term geographical isolation is likely the major factor that shaped the genetic structure of contemporary populations in Japan, while modern human uses are likely the major factor in continental East Asia.